Examining spillover effect of US monetary policy to European stock markets: A Markov-Switching approach - Zubair Mumtaz, Muhammad; Alexander Smith, Zachary (Estudios de Economía, 2019)
This study empirically examines the spillover effect from US monetary policy to nineteen European economies using Markov-switching models. The results of the univariate Markov-switching models validate the presence of two distinct regimes for both US monetary policy and the stock markets. We find mixed results when applying the multivariate Markov-switching models. The results report a positive relationship between the US interest rate and developed stock markets except for the Finish, Swiss, Swedish and UK stock markets whereas our findings confirm a positive relationship with the developing stock markets except for the Slovenian and Ukraine stock markets. Importantly, the nature of this effect varies during the economic crisis period. This study also compares the spillover effect between Asian and European stock markets and concludes that the effect of US monetary policy varies from market to market, however, changes in US monetary policy have greater effects on developed markets.